Perancangan Dan Analisis Statik Sistem Rangka Asykar Proto Mobil Hemat Energi - Teguh Iman; Syafri Syafri; Nazaruddin Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In design a car, it was necessary to pay attention to the frame structure design to get safety and comfort in driving. The frame design process starts with frame selection and material selection, followed by manual static calculation and stress analysis simulation using Autodesk Inventor 2017. The forces obtained by the frame comes from the weight of the driver, engine, and the body of the car. After the frame design has done, we get the results of the frame with a length of 2700 mm, a width of 550 mm and a height of 565 mm, this is based on the body shape of the car, driver, and available engine. The material of frame is a profile rod rectangular hollow 40 mm x 20 mm x 2 mm and square hollow 40 mm x 40 mm x 2 mm. In the static simulation obtained the greatest stress occurs in the main rod with a value of 100.8 MPa, and with the selection of the safety factor value of 4, so that the material suitable for use is carbon steel ST37. From the simulation results obtained the minimum safety factor value with a value of 1.83 but only in one small area in the frame.Keyword : frame, static analysis, stress, safety factor, Autodesk Inventor